Current and Future Needs of Gerontological Social Work Practice in Alberta: Findings from the World Café at the Gerontological Symposium in Edmonton, Canada. Issue 8 (17th November 2022) - Azulai, Anna; Tong, Hongmei; Quinn, Kathaleen; Mykietka, Kelly
ABSTRACT: The growing aging population in Canada has multi-faceted psycho-social needs. Social workers are well-positioned to address these needs, despite many challenges. This paper reports findings from the World Café at the Gerontology Symposium in Alberta, Canada, held in 2018. The goal was to learn from social work practitioners, researchers, and educators ( N  = 49) about current and future needs of gerontological social work in Alberta. There were two research questions: 1) What strategies do social workers need on the micro, mezzo, and macro levels to help better serve the growing older adult population in Alberta? (R1) 2) How can social workers promote the value and contribution of gerontological social work within the interprofessional community? (R2) The data were analyzed using qualitative content analysis. Ten R1-related themes emerged: personal traits of a social worker; professional skills; bio-psycho-social needs of older adults; community connections; access to benefits; gerontological social work education; integrated healthcare; aging policy; ageism; and advocacy to strengthen the voice of older adults. The three R2-related themes include strengthening the status of the social work profession; building trust through demonstrated skills; and interprofessional education and practice.